Successful resolution of mesenteric tuberculosis and HIV co-infection following 6 months of anti-tuberculosis therapy: a case report - Maulidiyah, Novita; Wicaksono, Ramadi; Retnowulan, Aisyah; Santoso, Budi; Subianto, Aries; Mashudi, Latifah; Kurniawan, Fajar (Deka in Medicine, 2024)
BACKGROUND: Mesenteric tuberculosis (TB), a rare extrapulmonary variant of TB, poses diagnostic and therapeutic challenges in its management. Therefore, discussing a case of mesenteric TB is both intriguing and informative for gaining insights into its clinical presentation and optimal treatment strategies. CASE PRESENTATION: A 50-year-old male presented symptoms of blackish stools three days post-gallstone surgery, accompanied by approximately two months of abdominal discomfort, described as squeezing or stabbing, alleviated temporarily by analgesics, alongside abdominal distension, rigidity, decreased appetite, and afternoon fevers. Physical examination revealed normal vital signs, with pale conjunctiva and asymmetrical chest wall movement, dull percussion, and decreased breath sounds in the lower left hemithorax. Abdominal inspection indicated distension, postsurgical signs, and ascites. Following laboratory investigations, chest and abdominal radiographs, and tissue biopsies, the patient was diagnosed with HIV co-infection along with pulmonary and mesenteric TB. Treatment comprised an intensive phase of four fixed-dose combinations (FDC) of anti-TB drugs, followed by a continuation phase of two FDC tablets, alongside first-line antiretroviral (ARV) therapy and cotrimoxazole prophylaxis. By the sixth month follow-up, clinical improvement was observed, with resolution of symptoms and weight gain to 56 kg. CONCLUSION: This case highlights the effective management of mesenteric TB and HIV co-infection, emphasizing the importance of comprehensive care and collaborative efforts between TB and HIV/AIDS control programs.